Effect of Chemical Doping on Cathodic Performance of Bicontinuous Nanoporous Graphene for Li‐O2 Batteries. Issue 3 (30th November 2015) - Han, Jiuhui; Guo, Xianwei; Ito, Yoshikazu; Liu, Pan; Hojo, Daisuke; Aida, Tsutomu; Hirata, Akihiko; Fujita, Takeshi; Adschiri, Tadafumi; Zhou, Haoshen; Chen, Mingwei
Abstract : Chemically doped graphene with three‐dimensional bicontinuous nanoporosity is developed for rechargeable Li‐O2 batteries. N and S doping, together with a large accessible surface area and open pore channels of the nanoporous graphene significantly enhance the cathodic reaction kinetics of Li‐O2 batteries for an ultrahigh rechargeable capacity of 10 400 mAh g −1 and a long cycling lifetime.